Brand Positioning and Segmentation of Sneakers through Multi-Dimensional Customer Experience Analysis - Senthilkumar, R.; RubanRaja, B.; Monisha, - (Journal of Scientific Research, 2021)
A huge corpus of valuable information on customer experience is available as unstructured form in customer reviews on e-commerce websites. Multivariate data analysis techniques are effective in uncovering hidden patterns and segments in structured data. A major challenge is to convert the unstructured data into a structured form for applying multivariate techniques. In this article, we have provided a text analysis based approach coupled with multivariate techniques to uncover the sentiment of various features associated with different brands and to determine the brand positions and segments through perceptual mapping and cluster analysis.